Personal bankruptcy in the Czech Republic: Age and gender of the debtors and structure of the creditors - Jan Hospodka; Ondřej Buben; Monika Randáková; Jiřina Bokšová (European Financial and Accounting Journal, 2017)
This paper analyses debtors who applied for debt relief in the period between 1/1/2012 and 31/12/2013. As there has already been a research related to Moravian and Silesian regions in this matter, it focuses mainly on the debtors from Bohemian regions. It is therefore an analysis of a problem which has not been thoroughly covered nor published yet. New way of declaring bankruptcy, in other words debt relief, for debtors who are unable to repay their debt has been in action since 2008. Since then the number of personal bankruptcies has been gradually rising every year. This paper constitutes only a narrow section of broader research; therefore, only certain characteristics are covered. Those are age and gender of the debtors and the structure of the creditors in all of the regions. The results and information gathered during the research are being analysed and also compared among particular regions.
Keywords: G33; K35; M41; 650; Bankruptcy; Czech Republic; Debtors